(untitled) (Journal of the College of Basic Education, 2022)
The external morphology of leafhopper belong to the genus Zelopsis sp. Evans 1966a, has been described. External morphological characters of the head, thorax and their appendages were used and abdomen of (male and female). Those characters were supported by study the male and female genitalia.